Asālib al-Ma’āni fī al-Şaḥīfah al-Sajādiyyah; Dirāsah Taḥlīliyyah Balāgiyyah: The Methods of Meanings in Saḥifa al-Sajjadiyah: An Analytical Rhetorical Study - Wushishi, Ibrahim Adam; Ghaderi, Fatemeh (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This is a paper entitled “The Methods of Meanings in Saḥifa al-Sajjadiyah: an Analytical Rhetorical Study,” which aims to reveal the methods of meanings in this aforementioned paper and reveal the power of expression and the rhetorical jokes that lie behind his expressions, peace be upon him. As well as the connotations of words, as they were in the era when the Imam used to deliver these words and sayings, and this sheet is filled with examples of these, such as the connotation of a word on the meaning in its utterance. And on the meaning in its sense that agrees or disagrees, or on the meaning according to the requirement. The general expression indicates the generality of its individuals, and the general expression indicates an individual that is not specific among its individuals, and the general expression is subject to restriction by any of the restricted words. The wording of the imperative requires a firm request. Finally, the most important results reached by this research come, and thus we can give a clear idea of the stages that the journey of rhetorical research passed through, the movement of semantics and its methods in Sahifa al-Sajjadiyyah, and the rhetoric movement in ancient and modern times. Thus, you discover the great role that the newspaper played in the field of scientific rhetorical research. The science, culture, thought and literature they provided to human civilization has benefited humanity - without a doubt - throughout its journey extending from the beginning of rhetoric until the beginning of the modern era. May God grant success and guidance to the straight path.